Analisis Tindak Tutur Representatif Coki Pardede Dalam Tayangan Video Why So Serious? Pada Kanal Youtube Malaka Project - Elfa Fadilah; Ari Muhammad Widyatama; Isma Ihsani; Rangga Samudra; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy; Rossi Galih Kesuma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
YouTube videos are one of the media that disseminate information quickly and can be reached by all circles of society. One of the YouTube videos that disseminates useful information is the Malaka Project YouTube channel which has the goal of realizing a golden Indonesia in 2045. The purpose of this study is to analyze the types and forms of representative speech acts contained in the Why So Serious? video hosted by Coki Pardede. Representative speech acts bind the speaker to the truth conveyed. This research article uses a theoretical approach, namely a pragmatic approach by analyzing the types and forms of representative speech acts. The research used descriptive qualitative method to analyze related data. The data were obtained from five videos in the Why So Serious? section of the YouTube channel, and the data collection technique used listening and recording techniques. Researchers listened to the Why So Serious videos, then recorded and recorded utterances that contained representative speech acts. The data analysis technique used pairing technique to examine the representative speech acts. From the data analysis that has been done, it is found that the representative utterances state, demand, admit, report, show, mention, testify and speculate. The results of the analysis in this article are expected to add a deeper understanding and knowledge of representative speech acts and their uses, knowledge of their types, as well as the types of representative speech acts.